2015
DOI: 10.1039/c5py00459d
|View full text |Cite
|
Sign up to set email alerts
|

Chemically crosslinked yet reprocessable epoxidized natural rubber via thermo-activated disulfide rearrangements

Abstract: Disulfide crosslinks introduced into an ENR matrix enable the thermo-activated reprocessing of the chemically crosslinked rubber, studied in terms of stress relaxation and adhesion experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
222
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 268 publications
(227 citation statements)
references
References 36 publications
2
222
1
2
Order By: Relevance
“…As the temperature is further increased to 100 °C, almost 84% release of the internal stress within 60 min can be obtained. The relaxation time τ was determined at 37% (1/e) of the initial relaxation modulus, which was based on the the Maxwell model for viscoelastic polymers (eq ): σtrue(ttrue)=σ0et/τ …”
Section: Resultsmentioning
confidence: 99%
“…As the temperature is further increased to 100 °C, almost 84% release of the internal stress within 60 min can be obtained. The relaxation time τ was determined at 37% (1/e) of the initial relaxation modulus, which was based on the the Maxwell model for viscoelastic polymers (eq ): σtrue(ttrue)=σ0et/τ …”
Section: Resultsmentioning
confidence: 99%
“…DTDB is an organic sulfur compound used in diverse technical applications, such as in the production of chemically crosslinked epoxidized natural rubber [11] and as an alternative monolayer for protein chips [12, 13]. Furthermore, DTDB is considered as an alternative promising substrate for PTE synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, as recently reviewed by our group9, only a limited number of associative exchange chemistries101112131415161718192021222324 have been explored in the context of vitrimers, and one of the main challenges is the precise control of the exchange kinetics. Although Leibler and co-workers demonstrated that epoxy-based transesterification vitrimers can be controlled by changing catalysts8, the exchange reaction remains slow and high catalyst loadings and temperatures are required to enable processing in a reasonable timeframe678.…”
mentioning
confidence: 99%